Reducing Nephrotoxicity Risk: A Collaborative Audit Of Nursing Assessment, Pharmacist Consults, And Radiology Contrast Administration (The Review of Diabetic Studies, 2024)
Acute Kidney Injury (AKI) due to nephrotoxicity from medications and contrast media is a major contributor to patient morbidity and hospital cost, with incidence rates approaching 20% in critically ill populations. This literature review evaluates the evidence supporting a collaborative, interprofessional approach to risk mitigation across three critical specialties: Nursing, Pharmacy, and Radiology. The review synthesizes findings demonstrating that each discipline offers unique, evidence-based protection. Nursing is essential for baseline GFR verification, precise volume status assessment using clinical metrics, and timely communication of risk changes. Pharmacy provides dose optimization via therapeutic drug monitoring (TDM) for narrow-index drugs and proactively manages complex drug-drug and drug-contrast interactions through clinical decision support alerts. Radiology is primarily responsible for minimizing contrast volume, selecting appropriate low-osmolar media, and dictating pre-/post-procedure hydration protocols based on established guidelines. The synthesis reveals that the primary failure point in prevention is often the lack of seamless communication during transitions of care, particularly concerning GFR changes and medication holds. Optimal nephroprotection requires unifying these specialized actions into a synchronized, system-wide workflow, emphasizing the Electronic Health Record as the critical tool for enforcement and collaborative communication.